Acute Systemic Viral Infection Masquerading as an Infiltrating Lymphoma in an Elderly Patient: A Case Report and Review of the Literature - Hani M. Babiker; Troy Wiedenbeck; Ryan S. Robetorye; Utkarsh Acharya; Susan Wilansky; Shimon Kusne (Case Reports in Medicine)
Primary Epstein-Barr virus (EBV) infection occurs mainly in adolescents and young adults, with more than 90% of adults having serological evidence of past infection. Primary infection in those over the age of 40 is associated with an atypical and often more severe presentation that can lead to more extensive and invasive, and often unnecessary, diagnostic testing. The incidence of severe EBV-related illness in older adults has been observed to be increasing in industrialized nations. The characteristic presentation of infectious mononucleosis (IM) syndrome in elderly patients (age > 65) is not clearly defined in the literature. Here, we describe a case of primary EBV infection in an 80-year-old female and review the literature regarding primary seroconversion in elderly patients.